2011
DOI: 10.1002/app.35408
|View full text |Cite
|
Sign up to set email alerts
|

Crack initiation of natural rubber under high temperature fatigue loading

Abstract: Vulcanized natural rubber (NR) under quiescent thermal oxidation aging and high temperature fatigue loading with small strain amplitude was investigated by the infrared spectroscopy, scanning electron microscopy, and positron annihilation lifetime spectroscopy measurements. IR results demonstrated the thermal oxidation degradation process of vulcanized NR at 85 C. During high temperature fatigue loading, nanoscale cracks and voids that are generated by the combined impact of thermal oxidation and cyclic loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The constitutive constants C 10 and C 01 are subsequently obtained by letting the derivatives of the errorsquared sum function d with respect to C 10 and C 01 equal zero, such that ∂d ∂C 10 = 0…”
Section: Prediction Of the Fatigue Life Of The Rubber Mountmentioning
confidence: 99%
See 2 more Smart Citations
“…The constitutive constants C 10 and C 01 are subsequently obtained by letting the derivatives of the errorsquared sum function d with respect to C 10 and C 01 equal zero, such that ∂d ∂C 10 = 0…”
Section: Prediction Of the Fatigue Life Of The Rubber Mountmentioning
confidence: 99%
“…Only a few studies have explored fatigue life estimation methods for rubbers operating in a high-temperature environment. 2,9,10 Hussain et al 2 investigated and compared the mechanical properties and the fatigue lives of dumbbell rubber specimens subjected to uniaxial tension at 23°C (room temperature) and 40°C. The study concluded that exposure to a temperature of 40°C yields a lower tensile stress and a reduction in fatigue life compared with those at 20°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It implies that there are more new surface created for the NR/FLIR 3 ‐ g ‐silica 10 sample . It is known that the crack propagation is concerned with cracking surface energy dissipation . So, it indicates that more energy is needed for cracking.…”
Section: Resultsmentioning
confidence: 99%
“…In the actual storage and application process, rubber products are often in various environments and will be affected by oxygen, ozone, ultraviolet rays, and heat [44][45][46][47].…”
Section: Rubbermentioning
confidence: 99%